DETERMINAN PENGUNGKAPAN RISIKO PADA PERUSAHAAN NONKEUANGAN DI INDONESIA - Yogi Utomo; Anis Chariri (Diponegoro Journal of Accounting, 2014)
The aim of this study is to examine the determinants of risk disclosure on non-financial companies in Indonesia. The population of this study is non-financial companies listed on the Indonesia Stock Exchange in 2012. Sampling is done by using purposive sampling method. Sample of this study is consisted of 335 non-financial companies in Indonesia. Hypothesis are tested by multiple regression analysis. The results showed that the ownership structure, independent directors and audit committees did not significantly affect the risk disclosures, while leverage, type of industry, and frequency of board meetings have positive significant effect in risk disclosures. The higher the leverage, the more complex type of industry, and the higher frequency of board meetings may enhance the risk disclosures on the companies.